2017
DOI: 10.22201/cgeo.20072902e.2017.3.485
|View full text |Cite
|
Sign up to set email alerts
|

Pómez Bosque de Tlalpan, producto de una erupción de gran magnitud en el margen suroeste de la cuenca de México

Abstract: In this contribution we describe a white pumice fall deposit, informally named pómez Bosque de Tlalpan (PBT), found in several outcrops v. 34, núm. 3, 2017, p. 274-288 Pómez Bosque de Tlalpan, producto de una erupción de gran magnitud en el margen suroeste de la cuenca de México

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…It consists from north to south of the La Catedral, La Bufa, Iturbide, Chimalpa, Salazar, San Miguel, Ajusco, La Corona, and Zempoala volcanoes, as well as other smaller structures (García-Palomo et al, 2008). Each volcanic structure has produced lava flows and domes that built the highest parts of these structures, while pyroclastic deposits, interbedded with lahar and debris avalanche deposits constitute the lower portion of the relief (fan-like morphology) surrounding the volcanic edifices (see the Main Map; Arce et al, 2008;Arce, Cruz-Fuentes, Ramírez-Luna, Herrera-Huerta, & Girón-García, 2017;Arce, Layer, et al, 2015). In this work we report a total of 14 new 40 Ar/ 39 Ar data, either whole-rock and mineral concentrate (see Table 1) to complement the available isotopic ages of this volcanic range.…”
Section: Miocene Volcanics -Tepoztlán Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…It consists from north to south of the La Catedral, La Bufa, Iturbide, Chimalpa, Salazar, San Miguel, Ajusco, La Corona, and Zempoala volcanoes, as well as other smaller structures (García-Palomo et al, 2008). Each volcanic structure has produced lava flows and domes that built the highest parts of these structures, while pyroclastic deposits, interbedded with lahar and debris avalanche deposits constitute the lower portion of the relief (fan-like morphology) surrounding the volcanic edifices (see the Main Map; Arce et al, 2008;Arce, Cruz-Fuentes, Ramírez-Luna, Herrera-Huerta, & Girón-García, 2017;Arce, Layer, et al, 2015). In this work we report a total of 14 new 40 Ar/ 39 Ar data, either whole-rock and mineral concentrate (see Table 1) to complement the available isotopic ages of this volcanic range.…”
Section: Miocene Volcanics -Tepoztlán Formationmentioning
confidence: 99%
“…In the San Lorenzo Tezonco and Mixhuca 1 deep wells, ignimbrite samples have been dated at 3 Ma (Arce, Layer, Morales-Casique, et al, 2013), which coincides with the age reported for this volcanic structure. Recently, Arce et al (2017) reported a pumice rich fallout in the southern part of the basin, dated at 37 ka. This deposit represents the most recent eruptive event of Sierra de las Cruces, which therefore increases the time interval over which the volcanoes of this range were active.…”
Section: Miocene Volcanics -Tepoztlán Formationmentioning
confidence: 99%
“…100 m-high hills located in the study area (Zacatépetl and Zacayuca, blue on Figure 6). Those present a thick cover of clayey soils that is locally overlaid by the same pumice layer detected at Viaje a la Naturaleza, which is fresher, better exposed and reaches a maximum thickness of 3 m in the Bosque de Tlalpan (Palacio and Guilbaud 2015; Arce et al 2017). At the lower part of these hills, several-m large, rounded crystal-rich blocks outcrop (Figure 7d); we interpret these blocks as the inner part of deeply eroded domes.…”
Section: Viaje a La Naturaleza Park And Study Areamentioning
confidence: 62%
“…As for the other park, products display a great variation in chemical composition from basaltic (Xitle), through basaltic andesitic (Viaje a la Naturaleza Kipuka), to dacitic (Zacayuca Kipuka). In terms of ages, in addition to the Xitle, only the altered pumice layer has been dated, with an age of about 30 ka (Arce et al 2017). The origin of such product is poorly defined but, based on its dacitic composition, it probably emitted by a volcano of the Sierra de Las Cruces (Arce et al 2017).…”
Section: Viaje a La Naturaleza Park And Study Areamentioning
confidence: 99%
“…The México Basin (Fig. 1b) is an endorheic basin closed by the Sierra de Las Cruces Volcanic Range (SLCVR, Mora-Alvarez et al, 1991;Arce et al, 2017) to the west, the SNVR to the east (Nixon, 1989;Cadoux et al, 2011;Macías et al, 2012), and the Sierra Chichinautzin Volcanic Field (SCVF, Siebe et al, 2004;Jaimes-Viera et al, 2018) to the south. The basin closed ~1 Ma ago, when monogenetic cones and lavas of the SCVF blocked drainage to the south resulting in the lower México Basin gradually filling with water (Mooser, 1963;, and facilitating the rapid accumulation of lake sediments (e.g., Martínez-Abarca et al, 2021).…”
Section: Geological Framework and Volcanic Evolution Of The Sierra Ne...mentioning
confidence: 99%